1997
DOI: 10.1055/s-2007-979113
|View full text |Cite
|
Sign up to set email alerts
|

Role of Superoxide Anions in Changes of Endothelial Vasoactive Response during Acute Hyperglycemia

Abstract: The effects of acute hyperglycemia on endothelial Ca2+ signaling, formation of endothelium-derived relaxing factor (EDRF) and bioactivity of EDRF were investigated. Hyperglycemia increased 2,5-tert-butyl-1,4-hydrochinone (BHQ)-initiated Ca2+ signaling and EDRF formation in a concentration-dependent manner. The effect of elevated D-glucose on Ca2+/EDRF response could be diminished by co-incubation with the antioxidants vitamin E, probucol, GSH, vitamin C and superoxide dismutase. Convincingly, hyperglycemic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 5 publications
(6 reference statements)
5
34
0
Order By: Relevance
“…3) could reorganise the architecture of the cytoskeleton, modulate Ca 2+ -sensitive/-activated transcription factors and signal cascade enzymes resulting in altered gene expression [136,190,191,192] (for review see [135]). In line with these data in beta cells, in endothelial cells the 54,193,194,195,196,197]. Thereby, the impact of Ca 2+ on gene expression exceeded its role in the nuclear envelope, where Ca 2+ is essential for modulating immediate early genes by modulating the DNA-binding of transcription factors (e. g. cAMP-responsive element binding protein CREB [191,192,198,199,200]).…”
Section: Nomentioning
confidence: 54%
“…3) could reorganise the architecture of the cytoskeleton, modulate Ca 2+ -sensitive/-activated transcription factors and signal cascade enzymes resulting in altered gene expression [136,190,191,192] (for review see [135]). In line with these data in beta cells, in endothelial cells the 54,193,194,195,196,197]. Thereby, the impact of Ca 2+ on gene expression exceeded its role in the nuclear envelope, where Ca 2+ is essential for modulating immediate early genes by modulating the DNA-binding of transcription factors (e. g. cAMP-responsive element binding protein CREB [191,192,198,199,200]).…”
Section: Nomentioning
confidence: 54%
“…Notably, endothelial Ca 2+ signalling has been shown to be a suitable marker for cell dysfunction initiated by a variety of stimuli such as E. coli lipopolysaccharides (LPS; [19]), peroxides [20,21,22], oxidized low density lipoprotein [23], streptozotocininduced diabetes [24,25] and hyperglycaemia [10,11,26]. The latter was causally linked to generation of · O 2 -in EC [10,27]. In line with these reports, the interaction of EC with high D-glucose pre-exposed SMC augmented the increase in cytosolic Ca 2+ in response to bradykinin.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of endothelial cells treated with high glucose in culture showed that high glucose-induced superoxide formation leads to an increase in intracellular calcium that activates endothelial NOS (NOS3) to form NO, but also causes NOS3 "uncoupling" to generate superoxide as well as NO (Fig. 10) (El-Remessy, 2003a;Graier et al, 1999;Graier et al, 1997;Graier et al, 1996) resulting in peroxynitrite formation. Research demonstrating increased levels of the peroxynitrite biomarker nitrotyrosine in retinas of diabetic patients and experimental animal models supports this concept and implies a role for peroxynitrite in the development of diabetic complications (Abu El-Asrar et al, 2004;Du et al, 2002;ElRemessy, 2003b;Kowluru and Odenbach, 2004;Obrosova et al, 2005).…”
Section: Oxidative Stress and Diabetic Retinopathymentioning
confidence: 99%